The Significance of German World War II Fortifications in the Defence of Klaipėda City in 1944–1945 - Tamkvaitis, Titas (History / Istorija, 2023)
Abstract. The article analyses the significance of the fortification complexes created by the German army in the period of the military actions between the German and the USSR forces for the city of Klaipėda from October 1944 to January 1945. The study focuses on the system of anti-aircraft and coastal artillery batteries of the German Navy in Klaipėda and the defence section, consisting of five defence lines, between the cities of Šiauliai and Klaipėda created by the German army in the second half of 1944. In order to assess the significance of the system of anti-aircraft and coastal artillery batteries, as well as the defensive lines established between the cities of Šiauliai of Klaipėda, the cases of these objects use and effectiveness during the battles (taking into account the structure, location, ranges of firing and other technical aspects) are highlighted in the context of the overall military actions of the German and the USSR forces during the period from October 1944 to January 1945.